$75 annual limit for CM hampers stimulant addiction treatment. Issue 10 (15th September 2020) - Knopf, Alison
Abstract : In August, the federal Department of Health and Human Services (HHS) doubled down on constraints against contingency management (CM), the best treatment for stimulant use disorders. This ruling by the HHS Office of Inspector General (OIG) comes at the same time that HHS releases $1 billion for State Opioid Response (SOR) funds, which, for the first time, can be used for stimulant use disorders as well. It also comes just as stimulant use disorders are on the verge of taking over the opioid epidemic.